Efficient synthesis of biazoles by aerobic oxidative homocoupling of azoles catalyzed by a copper(i)/2-pyridonate catalytic system - Zhu, Mingwen; Fujita, Ken-ichi; Yamaguchi, Ryohei (Chemical communications (Cambridge, England), 2011)
A highly efficient and convenient CuCl/2-pyridonate catalytic system for oxidative homocoupling of azoles affording a biazole product has been developed. With this system, a variety of biazoles have been effectively synthesized in good to excellent yields in the presence of a very small amount of copper catalyst (1.0 mol%). It was feasible to employ air as a green oxidant.